Susceptibility of herpes simplex virus type 1 to monoterpenes thymol, carvacrol, p-cymene and essential oils of Sinapis arvensis L., Lallemantia royleana Benth. and Pulicaria vulgaris Gaertn - Sharifi-Rad, J.; Salehi, B.; Schnitzler, P.; Ayatollahi, S. A.; Kobarfard, F.; Fathi, M.; Eisazadeh, M.; Sharifi-Rad, M. (Cellular and Molecular Biology, 2017)
In recent years, with increased the prevalence of viral infections and having no specific for their treatment and also the continuous appearance of resistant viral strains, the finding of novel antiviral agents is necessary. In this study, monoterpenes of thymol, carvacrol, p-cymene and essential oils from Sinapis arvensis L., Lallemantia royleana Benth. and Pulicaria vulgaris Gaertn. were screened for their inhibitory effect against herpes simplex virus type 1 (HSV-1) in vitro on Vero cell line CCL-81-ATCC using a plaque reduction assay. The antiviral activity of three monoterpenes (thymol, carvacrol and p-cymene) and three essential oils were evaluated by cytotoxicity assay, direct plaque test. In addition, the modes of antiviral action of these compounds were investigated during the viral infection cycle. Results showed that the inhibitory concentrations (IC50) were determined at 0.002%, 0.037%, >0.1%, 0.035%, 0.018% and 0.001% for thymol, carvacrol, p-cymene, S. arvensis oil, L. royleana oil and P. vulgaris oil, respectively. A manifestly dose-dependent virucidal activity against HSV-1 could be exhibited for compounds tested. In order to determine the mode of the inhibitory effect, compounds were added at different stages during the viral infection cycle. At maximum noncytotoxic concentrations of the compounds, plaque formation was significantly reduced by more than 80% when HSV-1 was preincubated with p-cymene. However, no inhibitory effect could be observed when the compounds were added to the cells prior to infection with HSV-1 or after the adsorption period. Conclusion: These results indicate that compounds affected HSV-1 mostly before adsorption and might interact with the viral envelope. Thymol exhibited a high selectivity index and seems to be a promising candidate for topical therapeutic application as antiviral agent for treatment of herpetic infections.